Parental feeding practices across child's weight status: Evidence of the Italian validation of the Child Feeding Questionnaire. Issue 6 (30th April 2021) - Buratta, Livia; Delvecchio, Elisa; Germani, Alessandro; Mazzeschi, Claudia
Abstract: Objective: The main aim of this study was to assess the psychometric proprieties of the Child Feeding Questionnaire (CFQ) in Italian mothers. Design: Mothers completed the Italian version of the CFQ, and children's anthropometric data were collected. Construct validity of the CFQ was assessed by comparing three different models: (a) a seven correlated factors model in which all items were analysed; (b) a seven correlated factors model with composite items based on the Restriction factor and (c) an eight correlated factors model with a separate Reward factor. Measurement invariance using BMI categories and gender was evaluated. Furthermore, discriminant validity with group comparison was performed between BMI categories and gender. Setting: Italy. Participants: A total of 1253 6-year-old Italian children (53·9 % male) attending elementary school (1st grade) and their mothers (mean age = 38·22 years; sd = 4·89) participated in this study. Results: The eight-factor model with a separate reward factor provided the best fit for the data. The strict invariance of the CFQ across child BMI categories and gender was confirmed. The CFQ internal consistency was acceptable for most subscales. However, two subscales showed no adequate values. As expected, the CFQ scales showed significant differences between BMI categories, while no gender-related differences were found. Conclusions: The study indicated the Italian version of the CFQ to be factorially valid for assessing parental feeding practices of 6-year-old children across BMI categories. Future research should address low internal consistency in some of the CFQ subscales.